The Effect of Liquidity, Leverage, and Firm Size on Firm Value with Profitability as a Moderating Variable - Supriyatna, Yoga; Akbar, Taufik (LifeSciFi, 2025)
In recent years, the Indonesian food and beverage sector has faced significant challenges, including rising raw material costs, declining purchasing power, and upcoming excise taxes, which have impacted stock prices and investor confidence. This study examines the effects of liquidity, leverage, and firm size on firm value, with profitability as a moderating variable. Employing a quantitative associative design, the research utilized a purposive sampling technique to select 28 companies from a population of 129 firms, observed over a three-year period (2021-2023). Data were analyzed using panel data regression in EViews 13. The results indicate that both liquidity and leverage have a significant positive impact on firm value. In contrast, firm size was found to have no significant effect. A key finding is the moderating role of profitability: it effectively strengthens the relationships between both liquidity and leverage with firm value. However, profitability was not a significant moderator for the relationship between firm size and firm value. These findings underscore the critical roles of financial structure and profitability in enhancing firm value, while suggesting that the influence of sheer size may be more nuanced or contingent on other factors not captured in this model.